The Role of Performance Political Stability and Macroeconomic Attracting Foreign Direct Investment in ASEAN - Maulidiyah, Ivada Nafiah; Fuddin, Muhammad Khoirul (Universitas Muhammadiyah Ponorogo, 2024)
Foreign direct investment (FDI) plays a crucial role in developing nations to raise the standard of living for their citizens and strengthen their economies. This research aims to investigate the effects of macroeconomic factors like GDP, inflation, and female employment in the industry on flows of foreign direct investment as well as factor political stability with a research focus on 5 ASEAN countries (Indonesia, Malaysia, Vietnam, Laos, Cambodia) with research 20 years. The research method used panel data regression with secondary data from the World Bank. The Fixed Effect Model is found to be the best model selection. The results showed that political stability variables as well as all macroeconomic fundamental variables as measured by GDP, Inflation, and Employment Females in Industry partially had a significant and positive effect on the inflow of Foreign direct investment in 5 ASEAN countries and simultaneously had a significant positive effect.